An Observational Prospective Cohort Study of Incidence and Outcome of Streptococcus pneumoniae and Hemophilus influenzae Infections in Adult Solid Organ Transplant Recipients - Rezahosseini, Omid (Microorganisms, 2021)
Background: Streptococcus pneumoniae (S. pneumoniae) and Hemophilus influenzae (H. influenzae) are among the main vaccine-preventable bacterial infections in immunocompromised individuals including solid organ transplant (SOT) recipients. There is a lack of information about incidence and outcomes of these infections in SOT recipients. Methods: We determined the incidence of S. pneumoniae and H. influenzae, the related hospitalization, and 30- and 180-days mortality in a large cohort of 1182 adult SOT recipients. We calculated 95% confidence intervals (CI) of incidence rate (IR) using Byar’s approximation to the Poisson distribution. Results: The overall IR of S. pneumoniae and H. influenzae were 1086 (95% CI, 796–1448) and 1293 (95% CI, 974–1687) per 100,000 person-years of follow-up (PYFU), respectively. The IR of invasive infections were 76 (95% CI, 21–202) and 25 (95% CI, 2.3–118) per 100,000 PYFU, respectively. Hospital admission was required in >50%, 30-days mortality was 0, and 180-days mortality was 8.8% and 4.5% after S. pneumoniae and H. influenzae infections, respectively. Conclusions: The IR of invasive S. pneumoniae and H. influenzae infections in SOT recipients were much higher than reports from the general population in Denmark. Furthermore, a large proportion of infected SOT recipients were hospitalized. These findings highlight the need for further studies to assess uptake and immunogenicity of vaccines against S. pneumoniae and H. influenzae in SOT recipients.